Glutathione S-Transferase Omega-2 and Transforming Growth Factor-β1 Polymorphisms in Iranian Glaucoma Patients. (23rd November 2021) - Bamdad, Shahram; Sanie-Jahromi, Fatemeh; Alamolhoda, Marzieh; Masihpour, Nasrin; Karimi, Mohammad-Hossein
Abstract : Background . To investigate the association of glutathione s-transferase omega 2 (GSTO2) (142N > D) and transforming growth factor- β 1 (TGF- β 1) (869T > C) gene polymorphisms on the pathogenesis of two common types of glaucoma (including primary open-angle glaucoma (POAG) and chronic angle-closure glaucoma (CACG)) in the Iranian population. Methods . A total of 100 glaucoma patients (60% males and 40% females with an age mean ± SD of 34.66 ± 14.25 years; 56 cases of POAG and 44 cases of CACG) were enrolled in this study. GSTO2 (142N > D) and TGF- β 1 (869T > C) polymorphisms were evaluated by PCR-based methods in patients and controls. Results . At locus GSTO2 (142N > D), the odds of ND genotype with respect to DD and NN genotypes were 1.55 and 2.08 times higher in POAG and CACG patients compared to those of patients in the control group (95% CI1 : 0.80–2.98; 95% CI2 : 1.00–4.33) which was statistically significant in CACG patients. However, the odds of DD and NN genotypes against the reference genotype in two patients group were not statistically significant as compared to those of patients in the control group. There was a significant association between the ND genotype and male patients (OR = 2.28, 95% CI: 1.06–4.92). The analysis of TGF- β 1 (869T > C) polymorphisms showed no significant difference between the genotypes of TGF- β 1 (869T > C) polymorphisms in patients and control groups; however, the CT genotype of TGF- β 1 significantly differed between female controls and patients (OR = 0.42, 95% CI: 0.18–0.96). Conclusion . The presented results revealed that there was a significant association between the ND genotype of GSTO2 and the pathogenesis of glaucoma. Furthermore, this genotype can be considered as a sex-dependent genetic risk factor for the development of glaucoma. In contrast, the CT genotype of TGF- β 1 is suggested to be a protective genetic factor against the pathogenesis of glaucoma.